IMAGERY IN THE ENGLISH TRANSLATION OF WANG WEI’S POEM AN AUTUMN NIGHT, SITTING ALONE - Erika Gunawati; Cayaputiyayi Tanuyanapat; I Gusti Agung Sri Rwa Jayantini (SPHOTA: Jurnal Linguistik dan Sastra, 2017)
ABSTRACT This study aims at describing imagery in the English translation of a Chinese poem written by Wang Wei, the great Chinese poet of Tang Dynasty. The focus of analysis is on imagery in the English translation of a Chinese poem entitled Qiuye Duzuo that is An Autum Night, Sitting Alone. It is interesting to analyze imagery in a poem to find out how vivid depiction of life is created through words. Through imagery, the readers of a poem can be brought into a certain situation that involves the human senses and part of body to see, hear, smell, touch and move. The identification of imagery in this study is based on Morner and Rausch (1998: 105) supported by the classification of imagery by Sayuti (2002). The results show that visual imagery is predominantly found in the poem that involves the eyes to see, meanwhile some lines can also be categorized as the auditory imagery that refers to images which involve the ears to hear. Key words: Imagery, Chinese Poem, ‘An Autumn Night, Sitting Alone.’